Religion, Toleranz, Rassismus im Wirkungsspektrum der Philosophie John Deweys – mit einem Seitenblick auf 100 Jahre „Demokratie und Erziehung“ - Retter, Hein (International Dialogues on Education Journal, 2016)
Religion, tolerance and democracy in the philosophy of John Dewey are at the centre of this contribution, with specific attention tho their contexts. In view of the escalating violence against Afro-Americans in the USA, which produces counterviolence, the question arises: What was the significance of tolence in Dewey’s conception of democracy? How successful was Dewey in using his pragmatic instrumentalism as a tool against open racism in American society? To answer these questions it is necessary to look at the origin and reception of pragmatism and the history of tolerance. A hundered years after the publication of „Democracy and Education, the the attempt of an answer leads to the realistic conclusion that Dewey’s educational philosophy promised more than it achieved. Two theses are discusssed: „Democracy and Education“ can only be fully understood against the background of a unity of democracy and religion in Dewewy’s early work. Secondly: Dewey’s social philosophy is a secular theology. While it could hardly reach the „color problem“ of American society, it was able to strengthen the belief in democracy.